PENGGUNAAN MICROSOFT TEAMS FOR EDUCATION UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA MELALUI MODEL PBL - Beny Yulianingsih (saintifika, 2021)
Learning activities are activities carried out to produce changes in knowledge and skills in students. Learning activities contribute to the learning outcomes that students will get. The purpose of this study was to determine the learning activities of class XI students on the respiratory system material online at Pakusari Public High School using Microsoft Teams for Education with the PBL model. This research is a quantitative descriptive research. The study population was all students of class XI SMA Negeri Pakusari. Student learning activities are categorized as beneficial because students take part in learning by carrying out various learning activities. The conclusion is that the average learning activity of class XI SMA Negeri Pakusari respiratory system material reaches 64,35%, including the very good category. The highest percentage is mental activity with a percentage of 71%. The activity that got the lowest percentage was drawing activity with a percentage of 55%.